Memória, testemunho e exílio no romance No exílio de Elisa Lispector - Santos, Vivian Leone de Araújo Bastos (2015)
This research focuses on literature produced by Elisa Lispector, immigrant writer who deals with sensitivity and uniqueness with the problematic of exile as well as the incommunicado in her literary composition. The corpus chosen for analysis is the novel No Exílio, first published in 1948. Considering the autobiographical traits constantly merged with the fiction in the novel, as pointed out by Nadia Battella Gotlib in text that is constitutes the unfinished and autobiographical work Retratos Antigos (2012), by Elisa Lispector, as well as the attempt to narrate Lispector family output a small village in Ukraine, where they lived, trying to escape the violence of the pogroms and the arrival into exile, i. e., in Brazil, in the early twentieth century. The very attempt to communicate this limit-experience and the pain of exile brings itself irrefutable testimonial traits, thus, in the wake of categories that problematize the modern world and its new conjucture permeated by disasters and traumas, seeking the support of Márcio Seligmann-Silva, especially of his studies in História, memória, literatura – o testemunho na era das catástrofes (2013), of Walter Benjamin in em A modernidade e os modernos (2000), of Friedrich Nietzsche in Genealogia da Moral (2012) and of Julia Kristeva com Estrangeiros para nós mesmos (1994), as well as other studies and theorists who have contributed significantly to the development and enrichment of research.